DEFINITION OF ARTISTIC DETAIL IN MODERN LITERARY CRITICISM - Ergashev , Asilbek Khamzaevich (Mental Enlightenment Scientific-Methodological Journal, 2025)
This article examines the artistic detail as a multi-layered and meaning-generating component of literary texts, emphasizing its structural and semantic significance. Contrary to viewing it as a minor narrative element, the detail is analyzed as a central expressive tool shaping the philosophical, psychological, and aesthetic dimensions of the work. The theoretical foundation relies on the scholarship of Russian literary critics such as A.B. Esin and V.A. Kukharenko, whose classifications form the methodological basis for applied textual analysis. The article examines specific literary examples — R. Töpffer’s The Path Beyond the Ocean, J. Steinbeck’s Escape, and V.N. Gavrilyeva’s The Road — illustrating how symbolic details reflect internal character dynamics, philosophical motifs, and thematic depth. Through the lens of romantic, naturalistic, and socio-psychological paradigms, the study demonstrates that artistic detail functions as a universal mechanism that bridges the particular with the universal and reveals the author's worldview through seemingly minor narrative elements.